Variação genética entre e dentro de populações de dipteryx alata vog. para caracteres morformétricos de plântulas, frutos e sementes - Luz, Kelly Cristina da [UNESP] (2016)
Dipteryx alata is considered endemic species of the Brazilian Cerrado. Currently the species needs attention by the increased fragmentation of the occurrence area. It stands out for presenting resistant wood and the high production of fruits. The aim of the study was to estimate genetic parameters from the morphometric fruits, seeds and seedlings, to provide information of genetic variability within and between species provenances for future breeding programs and conservation. The fruits were collected in three natural populations, as Campo Grande - MS, Ituiutaba - MG and Paulo de Faria - SP, in October 2014. The seedlings were prepared in the nursery Fazenda de Ensino, Pesquisa e Extensão (FEPE/UNESP). For morphometric analysis of fruits and seeds were measured (mm) thickness (mm) Length (mm) Mass (g). In the seedlings were evaluated the total height (cm) Stem diameter (mm). We used the design complete block design (RBD) with one plant per plot. There were statistically significant differences among provenances and progenies for the characters of fruits, seeds and seedlings, indicating the presence of genetic variation. The results of the average heritability coefficient of individual variation and accuracy, indicated that for the fruits, seeds and seedlings there is presence of genetic variability. In the analysis of all the seedlings can be seen that there were significant differences in the effect of origin and not significant for the effect of progeny. Results indicate that these materials may be used for genetic conservation of species and genetic improvement.